Comparative Efficacy of Chinese Herbal Injections for Septic Shock: A Bayesian Network Meta-Analysis of Randomized Controlled Trials - Huang, Peiying; Chen, Yan; Zhang, Haobo; Chen, Bojun; Zhao, Shuai; Feng, Yuchao; Lei, Sisi; Wu, Qihua (Frontiers in Pharmacology, 2022)
Background: Septic shock is associated with high morbidity and mortality. Studies have reported that Chinese herbal injections (CHIs) in combination with western medicine (WM) were more favorable. However, the debate on optimal CHIs is ongoing. The objective of this study is to explore the comparative effectiveness of CHIs for septic shock. Methods: We retrieved data from the English and Chinese databases with retrieval time from database inception to September 30, 2021. Network meta-analysis was performed, with evaluation of methodological quality among the included studies and assessment of strength of evidence among the outcomes. Results: A total of 77 RCTs with 5,647 patients were included. All the studies were rated as some concerns. In terms of 28-day-mortality, Yiqifumai injection (YQFM)+WM, Shuxuetong injection (SXT)+WM, Xuebijing injection (XBJ)+WM, and Shenfu injection (SF)+WM were better than WM; YQFM+WM and SXT+WM were superior for Shenmai injection (SM)+WM; YQFM+WM was superior for SF+WM; YQFM+WM ranked first. Regarding ICU length of stay, SF+WM and XBJ+WM were better than WM; XBJ+WM was superior for SF+WM; XBJ+WM ranked first. Concerning hospital length of stay, Shenqifuzheng injection (SQFZ)+WM, Shengmai injection (SGM)+WM, and XBJ+WM had greater potential than WM and SF+WM; SQFZ+WM ranked first. As for SOFA score at 7-day, XBJ+WM and SF+WM were superior for WM; XBJ+WM was superior for SF+WM; XBJ+WM ranked first. Regarding procalcitonin level at 7-day, SF+WM, SM+WM, and Xiyanping injection (XYP)+WM were better than WM; XYP+WM was superior for SF+WM, SGM+WM, SM+WM, Danshen injection (DS)+WM, and XBJ+WM; XYP+WM ranked first. Concerning serum lactate level at 7-day, SF+WM and SM+WM were more effective than XBJ+WM and WM; SM+WM ranked first. The comparisons were rated as moderate (15.05%), low (40.86%), and very low quality (44.09%); the strength of evidence of ranking probability for hospital length of stay was low whereas the remaining outcomes were rated as very low. Conclusions: CHIs combined with WM might have higher efficacies for septic shock than WM alone. YQFM, XBJ, SQFZ, XYP, SM, SGM, and SF may be the potential optimal CHIs for septic shock. More and better evidence is needed to validate the conclusions.